How Do Female Leadership Competencies Affect to Performance from a Customer Perspective? - Setiani; Maretha Ika Prajawati; Esy Nur Aisyah (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Objective: The study aims to explore the style of leadership of small business women by applying the theory of power competition to analyze competence influencing leadership in power SMEs competitiveness. Study will focus on the abilities for growth in a period longer than a profitability period short for SMEs. Ability growth is considered a fundamental factor for SMEs, so follow up a study about the influence of women in competence to SMEs performance growth. Research Design & Methods: A quantitative research (positivism). The research location is SMEs in Batu City with 98 respondents. Data analysis methods use validity, reliability, classic assumption, and hypothesis tests. Findings: The female leadership competencies with five dimensions (strategic visions, operation management, professional knowledge, hands-on experience, relationship building) have a positive and significant effect on performance from the perspective of consumers. Implications & Recommendations: The study is that it can provide an understanding of female leadership, that the spirit of competence within oneself needs to be developed so that the business that is built can progress and develop rapidly. Contribution & Value Added: The study expected to be able to provide information as a basis for consideration, support, and contribution of ideas to decision makers in an effort to be able to increase income and carry out business development.